2008
DOI: 10.1103/physrevb.78.155427
|View full text |Cite
|
Sign up to set email alerts
|

Spin and band-gap engineering in doped graphene nanoribbons

Abstract: We investigate electronic and magnetic properties of graphene nanoribbons whose edges are doped by s-, p-, and d-type atoms. The edges of the ribbon are chemically active and can accommodate appropriate dopants to obtain different electronic and magnetic properties, all with the same geometrical structure of the ribbon. Dopings by Mg and B turn the semiconducting armchair ribbon into a metal, while Fe and Mn change it into a ferromagnet with a large magnetic moment. Doping of zigzag ribbon and implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 24 publications
3
91
0
Order By: Relevance
“…29 This leads to impurity distributions heavily weighted towards the edge sites -an observation confirmed elsewhere in the literature. [30][31][32][33][34][35][36] In addition to the binding energy, the magnitude of the magnetic moment on an impurity atom should also depend on impurity position. We shall demonstrate here that the principal features of this dependence derive from the underlying electronic structure of the GNR host.…”
Section: -27mentioning
confidence: 99%
“…29 This leads to impurity distributions heavily weighted towards the edge sites -an observation confirmed elsewhere in the literature. [30][31][32][33][34][35][36] In addition to the binding energy, the magnitude of the magnetic moment on an impurity atom should also depend on impurity position. We shall demonstrate here that the principal features of this dependence derive from the underlying electronic structure of the GNR host.…”
Section: -27mentioning
confidence: 99%
“…[13][14][15] As quasi 1D materials, GNRs are extremely sensitive to their surrounding conditions, which provides a route for manipulating their electronic properties. Additionally, other factors such as finite size effect, 16,17 edge effect, [18][19][20][21][22][23] and the presence of strain [24][25][26][27] could be used to effectively tune the electronic properties GNRs.…”
Section: Introductionmentioning
confidence: 99%
“…Gorjizadeh et al 7 have reported the spin and band-gap controlling by ab initio calculation in doped GNRs. Park et al 14 In this paper, we present a spin dependent study on the electronic and transport properties of perfect and Be edge-doped ZGNRs.…”
mentioning
confidence: 99%
“…As we know, the substitutional doping of the alkaline earth metal Be atoms in Silicon is feasible. 15 The band structure of armchair GNRs doped with the alkaline earth metal Mg atoms has been calculated by N. Gorjizadeh et al 16 and our first principle calculation suggests that the substitutional doping of Be atoms in ZGNRs is stable. In the following, we use the 3-, ZGNRs so the interfaces between them have less effect on the transport than those in conventional metal -conductor -metal systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation